The Fight against the Forced Labor and the Human Trafficking in Central Asia - Leonid Yu. Gusev (Vestnik MGIMO-Universiteta, 2015)
The article deals with the combat of forced labor and human trafficking in Central Asia. It is noted that this problem has emerged since the early 90s, when these countries got the independence, due to the difficult economic situation, activity of extremist organizations. It is pointed out that the victims of trafficking may be men, women and children, but in most cases they are young women and girls who are sexually exploited. It is shown by the examples of each of the countries of the region, what is being done to counter this terrible phenomenon. The Government of the Republic of Tajikistan established the Interdepartmental Commission to Combat Human Trafficking. The commission, in cooperation with international organizations doing some work to inform the public, the search for victims of sexual business, return and rehabilitation of these persons. In Kazakhstan, according to the new law it has become easier to initiate criminal proceedings concerning labor slavery. In addition, a temporary accommodation center for victims of human trafficking «Komek» was created. In Kyrgyzstan, a working group on the development of 3 of the National Action Plan to Combat Trafficking in Human Beings (2011-2015) under the auspices of the Ministry of Labour, Employment and Migration of the Kyrgyz Republic was created. In Uzbekistan, the law «on combating human trafficking» came into force. In addition, a Republican Interdepartmental Commission to Combat Human Trafficking was created. The law defines the powers of public authorities directly involved in the activities in this direction. In Turkmenistan, the government prohibits all forms of trafficking of persons in accordance with Article 129 of the Criminal Code, adopted in May 2010 and entered into force in July 2010. It provides for penalties ranging from 4 to 25 years in prison. These penalties sufficiently stringent and commensurate with penalties prescribed for other serious crimes, such as rape. At the end of the article conclusions and recommendations are made.